DOMESTICATION AND FOREIGNIZATION IN THE TRANSLATION OF CHILDREN’S LITERATURE - M. Xamidova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  studies  domestication  and  foreignization  in  the  translation  of children’s literature. The topic is important because children’s books carry language, culture, values, humor, and daily life together. When a story is translated, the translator must decide whether to make the text closer to the young reader or preserve the foreign color of the source text. The article analyzes how this problem appears in culture-specific items, food names, proper names, and short rhythmic lines. The research is based  on  descriptive  translation  analysis,  close  reading,  and  comparative  textual analysis. Classical works by Lawrence Venuti, Riitta Oittinen, Gillian Lathey, Göte Klingberg,  and  Emer  O’Sullivan  are  used  together  with  newer  studies  by  Haidee Kruger,  Fenik  M.  Ghafur,  and  Kaveh  Bassiri.  Short  extracts  from  well-known children’s stories are examined to show how each strategy changes meaning, tone, rhythm, and cultural atmosphere. The main result is that children’s literature translation usually  works  best  when  a  balanced  method  is  used:  very  difficult  items  may  be adapted, but important cultural signs should remain visible.